Controlled Scalable Synthesis of Uniform, High-Quality Monolayer and Few-layer MoS(2 )Films - Yu, Yifei (Nature Publishing Group, 2013)
Two dimensional (2D) materials with a monolayer of atoms represent an ultimate control of material dimension in the vertical direction. Molybdenum sulfide (MoS(2)) monolayers, with a direct bandgap of 1.8 eV, offer an unprecedented prospect of miniaturizing semiconductor science and technology down to a truly atomic scale. Recent studies have indeed demonstrated the promise of 2D MoS(2) in fields including field effect transistors, low power switches, optoelectronics, and spintronics. However, device development with 2D MoS(2) has been delayed by the lack of capabilities to produce large-area, uniform, and high-quality MoS(2) monolayers. Here we present a self-limiting approach that can grow high quality monolayer and few-layer MoS(2 )films over an area of centimeters with unprecedented uniformity and controllability. This approach is compatible with the standard fabrication process in semiconductor industry. It paves the way for the development of practical devices with 2D MoS(2) and opens up new avenues for fundamental research.